Biologically active phenolic constituents from Alpinia gagnepainii K. Schum. (Zingiberaceae) - Tram, Le Huyen; Giang, Phan Minh; Son, Phan Tong (Vietnam Journal of Chemistry, 2014)
The fractionation of the MeOH extract from the rhizomes of Alpinia gagnepainii K. Schum. (Zingiberaceae) collected in province Lai Chau, Vietnam, was directed by the antibacterial activity against Gram-positive and Gram-negative bacteria as well as the free radical scavenging activity of the soluble fractions of the MeOH extract. β-Sitosterol, stigmasterol, cardamomin (2), 5,6-dehydrokawain (4), naringenin 5-O-methyl ether (5), and a new phenolic compound, designated alpininone (3), were isolated. Their structures were determined on the basis of spectroscopic analyses. (–)-Pinocembrine (1), which was isolated from A. gagnepainii K. Schum. collected in province Quang Binh, Vietnam, 2, and 3 showed a good correlation with the antibacterial activity of the soluble fractions, while 4 was selective against fungi. However 1-5did not demonstrate the free radical scavenging activity in the DPPH assay. Key words: Alpinia gagnepainii; Zingiberaceae; phenolic constituent; antimicrobial activity; free radical scavenging activity.